STUDY OF SOME BIOLOGICAL PROPERTIES NECROTIC ISOLAT OF POTATO VIRUS X AND PHYLOGENETIC ANALYSIS - V.Fayziev; Javlieva, D.; Kadirova, Z.; Chirkov, S.; Jurayeva, U.; Vakhabov, A. (International Journal of Psychosocial Rehabilitation, 2025)
As a result of studies with the study of X potato virus, a new “necrotic” virus isolate was isolated that was different from other outbreaks and its characteristics were studied in test indicator plants and the ORFs5 gene, which is responsible for the synthesis of the protein coat, has multiple variability. As a result of mechanical inoculation to the indicator isolate plants, it was revealed that the D. stramonium plant at the tips of the leaves shows signs of necrosis, while Nicotiana tabacum plant, in contrast to other isolates, shows signs of green mosaic. The molecular genetic properties of the isolate are carried out on the basis of the ORFs5 gene, which is responsible for the synthesis of its protein coat; as a result of phylogenetic analyzes, it was found that the PXVn isolate common in Uzbekistan has a homology of 97.48% with the exfoliated D003441.1 isolated in the Netherlands and has 97.06% homology with isolate GU384732.1 in Australia, isolates AY297843.1, AY297842.1 and M95516.1 in the UK. The revealed differences showed the ability to register this isolate studied in Uzbekistan as a new PVXn isolate and this isolate was placed on the NCBI PVXUZ base under the number MN702769.